A novel double-endoloop technique for natural orifice transluminal endoscopic surgery gastric access site closure - Hucl, Tomáš; Beneš, Marek; Kočík, Matěj; Krak, Martin; Malušková, Jana; Kieslichová, Eva; Oliverius, Martin; Špičák, Julius (Gastrointestinal endoscopy, 2010)
BACKGROUND: Effective and safe access site closure is critical for clinical application of natural orifice transluminal endoscopic surgery. OBJECTIVE: The current study evaluated a simple novel technique of gastrotomy closure. DESIGN: Feasibility study with a survival animal model. SETTING: Animal laboratory. SUBJECTS: Ten female domestic pigs. INTERVENTIONS: Endoscopic closure of a gastrotomy incision was evaluated in 10 pigs in a survival study. A standard double-channel endoscope was advanced into the peritoneal cavity through an incision made by a needle-knife and an 18-mm dilation balloon. After peritoneoscopy and salpingectomy, gastric closure was performed by using an endoscopic grasper and sequential application of 2 endoloops. After a follow-up period of 1 to 3 weeks, the pigs were killed for postmortem examination. MAIN OUTCOME MEASUREMENTS: Feasibility, efficiency, and safety of a novel closure technique. RESULTS: Correct positioning and delivery of endoloops was achieved in all animals in a median time of 17 minutes (range 13-25 minutes). All animals survived without complications. Postmortem examination demonstrated patent full-thickness gastric closure without any evidence of infection. LIMITATIONS: Feasibility study with a small number of subjects in a porcine model. CONCLUSION: Double endoloop technique represents a novel, simple, safe, and efficient means of gastric access site closure in natural orifice transluminal endoscopic surgery.
Keywords: žaludek; šicí techniky; laparoskopie; zvířata; Animals; Wound Healing; gastrostomie; Female; Swine; Laparoscopes; chirurgické nástroje; ženské pohlaví; Laparoscopy; prasata; Surgical Instruments; Suture Techniques; laparoskopy; hojení ran; Stomach; Gastrostomy